2020
DOI: 10.1101/2020.10.13.337667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycobacterial surface-associated ESX-1 virulence factors play a role in mycobacterial adherence and invasion into lung epithelial cells

Abstract: EsxA has been recognized as an important virulence factor of Mycobacterium tuberculosis (Mtb) that plays an essential role in Mtb cytosolic translocation by penetrating phagosomal membranes with its acidic pH-dependent membrane permeabilizing activity (MPA). Currently, the reported cytolytic activity of EsxA at neutral pH is controversial. In this study we have obtained direct evidence that it is the ASB-14, a detergent used in EsxA purification, but not EsxA that causes cytolysis at neutral pH. We have also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, we and others found that many of the pore-forming activities ascribed to ESAT-6, such as RBC lysis, was due to residual detergent contamination in ESAT-6 preparations made using standard, widely distributed protocols (8,23,24). Moreover, we found that true ESX-1-mediated RBC lysis was contact dependent and caused gross membrane disruptions as opposed to distinct pores (8).…”
mentioning
confidence: 56%
“…However, we and others found that many of the pore-forming activities ascribed to ESAT-6, such as RBC lysis, was due to residual detergent contamination in ESAT-6 preparations made using standard, widely distributed protocols (8,23,24). Moreover, we found that true ESX-1-mediated RBC lysis was contact dependent and caused gross membrane disruptions as opposed to distinct pores (8).…”
mentioning
confidence: 56%
“…This protocol had been used in several studies [ 28 , 50 , 187 ]. Our recent data show that even after several detergent removal procedures, the concentration of the residual ASB-14 in the purified EsxA still ranges from 12 to 32 μg/mL, which is enough to cause cell lysis [ 188 ]. In fact, instead of causing cytolysis, the exogenously added EsxA protein without ASB-14 is internalized into the lung epithelial cells and traffics to acidic subcellular compartments, where it inserts into the membranes [ 188 ].…”
Section: The Questions That Remain To Be Answeredmentioning
confidence: 99%
“…The Mm strain with the deletion of esxBA has an increased adherence to the murine macrophages [ 44 ]. Most recently, our preliminary data have shown that the Mm strain with EsxA deletion has an increased adherence but a decreased invasion in WI-26 [ 188 ]. Recent studies have shown that the secreted EsxAB remains associated with the mycobacterial cell wall, rather than released into the medium, and the cell wall-associated EsxAB correlates with bacterial virulence [ 85 , 198 , 204 ].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified ESAT-6, but not its co-secreted partner CFP-10, lysed artificial lipid bilayers, liposomes, and red blood cells (RBCs), leading to the conclusion that ESAT-6 functions as a classical pore-forming toxin (15,21,22). However, we and others found that many of the pore-forming activities ascribed to ESAT-6, such as RBC lysis, was due to residual detergent contamination in ESAT-6 preparations made using standard, widely distributed protocols (8,23,24). Moreover, we found that true ESX-1-mediated RBC lysis was contact-dependent and caused gross membrane disruptions as opposed to distinct pores (8).…”
Section: Introductionmentioning
confidence: 98%